Is food security a new tariff? Explaining changes in sanitary and phytosanitary regulations by World Trade Organization members - Kassatly, Raymond; Long, Andrew G.; Kastner, Justin J. (My University, 2013)
Scholars at the intersection of agricultural trade policy and health regulation have speculated that some governments, under the pretext of health protection, have adopted food safety and plant and animal health regulations to shield domestic farmers from foreign competition. In this paper, we investigate the relationship between trade protection for agriculture and the number of trade‐restricting sanitary and phytosanitary (SPS) regulatory notifications issued by World Trade Organization (WTO) members. We construct an empirical model to determine the influence of agricultural protectionism, agricultural interest groups, consumer sentiment, and institutional capacity on changes to a government’s SPS rules. The findings suggest that governments’ adoption of trade‐restricting sanitary and phytosanitary regulations are influenced by agricultural protectionism, even after controlling for consumer awareness and institutional capacity. The evidence suggests that health related trade policies are substituting for more traditional forms of agricultural protectionism.
Keywords: World Trade Organization; SPS Agreement; Sanitary and phytosanitary notifications; Agricultural protectionism; Consumer welfare; Consumer awareness